2009
DOI: 10.3141/2140-19
|View full text |Cite
|
Sign up to set email alerts
|

Bicycle Helmet Wearing among Adolescents

Abstract: Adolescents experience many benefits from bicycling; however, there are also potentially significant injury consequences. One effective counter-measure for the prevention of adolescent bicycling injuries is to promote bicycle helmet wearing. An overview is provided of injury risks of bicycle riding with particular attention to the role of helmet wearing and associated countermeasures such as legislation and school and community approaches. The findings are presented of a study conducted in Australia that exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have shown that children in Cambodia and elsewhere are strongly influenced by the helmet use behaviour of their peers; therefore, programmes such as HFK might have a role in building a broader road safety culture in families and communities where HFK is implemented. [18, 21, 30, 36, 37] The Cambodia Helmet Vaccine Initiative also implements population based interventions to encourage helmet use, such as behaviour change communication campaigns. Messages from the community based campaign and HFK are meant to be complementary to each other.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that children in Cambodia and elsewhere are strongly influenced by the helmet use behaviour of their peers; therefore, programmes such as HFK might have a role in building a broader road safety culture in families and communities where HFK is implemented. [18, 21, 30, 36, 37] The Cambodia Helmet Vaccine Initiative also implements population based interventions to encourage helmet use, such as behaviour change communication campaigns. Messages from the community based campaign and HFK are meant to be complementary to each other.…”
Section: Discussionmentioning
confidence: 99%